Research on Cluster Economy Operation Model Considering Customer Satisfaction - Wei Zhao; Wenqi Xue; Peiqiang Li; Xuexian Tang; Ertao Lei; Hanbin Diao; Xiaoxiu Lv (IEEE Access, 2022)
A Real-time electricity market transaction is an important method that is used to realize the interactive balance of source-network-load in a new generation power system. Based on the multi-camp economic choice and the needs of national conditions, the emergence of cluster operators is inevitable. Due to stability and development of photovoltaic users, it is important to evaluate the importance of users in a photovoltaic user group. In the existing model, users are too sensitive to the electricity price, which will lead to too high electricity adjustment rate. In order to make up for the lack of importance ranking research and the high adjustment rate of electricity consumption, this paper will introduce the electric power consumption satisfaction function and propose an optimal pricing model that is based on the master-slave game. The study analyzes the nature of operators’ revenue, and presents a method to calculate the contribution value using the cooperative game theory. The TOPSIS method is proposed to evaluate the ranking of the producers and sellers in the group. The developed illustration verifies the superiority of the cluster economic operation model.